2016
DOI: 10.1002/cssc.201501591
|View full text |Cite
|
Sign up to set email alerts
|

Direct Conversion of Greenhouse Gas CO2 into Graphene via Molten Salts Electrolysis

Abstract: Producing graphene through the electrochemical reduction of CO2 remains a great challenge, which requires precise control of the reaction kinetics, such as diffusivities of multiple ions, solubility of various gases, and the nucleation/growth of carbon on a surface. Here, graphene was successfully created from the greenhouse gas CO2 using molten salts. The results showed that CO2 could be effectively fixed by oxygen ions in CaCl2-NaCl-CaO melts to form carbonate ions, and subsequently electrochemically split i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 38 publications
(54 reference statements)
2
75
0
Order By: Relevance
“…[348][349][350] However, the research has remained fairly quiet until recent consideration of the process for capture and utilisation of CO2. [351][352][353][354][355][356][357][358][359][360] Particularly, electrodeposition and re-oxidation of carbon in molten carbonate salts under the CO2 atmosphere have been investigated in order to close the loop of CO2-carbon cycles via the combination of molten salt electrolysis and DCFCs for energy storage. 355,356 To help understand the carbon deposition process, different salt compositions have been used to investigate the electrochemical deposition and re-oxidation of solid carbon, which are CaCl2-CaCO3-LiCl-KCl (molar ratio of 0.30:0.17:0.43:0.10) and Li2CO3-K2CO3 (molar ratio of 0.62:0.38) at different temperatures and atmospheres.…”
Section: Direct Carbon Fuel Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…[348][349][350] However, the research has remained fairly quiet until recent consideration of the process for capture and utilisation of CO2. [351][352][353][354][355][356][357][358][359][360] Particularly, electrodeposition and re-oxidation of carbon in molten carbonate salts under the CO2 atmosphere have been investigated in order to close the loop of CO2-carbon cycles via the combination of molten salt electrolysis and DCFCs for energy storage. 355,356 To help understand the carbon deposition process, different salt compositions have been used to investigate the electrochemical deposition and re-oxidation of solid carbon, which are CaCl2-CaCO3-LiCl-KCl (molar ratio of 0.30:0.17:0.43:0.10) and Li2CO3-K2CO3 (molar ratio of 0.62:0.38) at different temperatures and atmospheres.…”
Section: Direct Carbon Fuel Cellsmentioning
confidence: 99%
“…Reducing this potential difference would benefit the energy efficiency of electrochemical cycling between CO2 and carbon, which may result from the fast growing interests and activities in this area. [350][351][352][353][354][355][356][357][358][359][360] …”
Section: Direct Carbon Fuel Cellsmentioning
confidence: 99%
“…al 11 The authors comment that the observed "nano ropes" observed are parallel carbon nanofibers bound together, though speculation of how the different carbon nanostructures are formed in electrolysis is not detailed in the report. In more recent years, the observation of higher quality carbon nanostructures has been studied, with the growth of few-layer graphene sheets (<5 layers) 15,16 ( Figure 5d) and carbon nanofibers with diameters >200 nm (Figure 5e) 58 in 2015, and more recently carbon nanotubes with diameters >100 nm (Figure 5f) 46 in 2016. These works begin to build upon mechanistic understandings gained from gas phase growth techniques, and start to bridge the gap between gas phase growth of carbon nanostructures and CO 2 electrolysis.…”
Section: Types Of Carbon Materials Produced From Comentioning
confidence: 99%
“…[42][43][44][45] In contrast to this mature field, the growth of carbon nanostructures from the liquid-phase electrochemical reduction of CO 2 remains only a new field of research, with the most recent work demonstrating growth of large-diameter (>100 nm) CNTs 46 and fewlayer graphene flakes from CO 2 conversion. 15,16 These initial works demonstrate the capability to leverage CO 2 as a precursor in carbon nanostructure growth, even though forward-looking efforts to achieve high quality, precisely tuned materials such as single-walled CNTs or single-layered graphene at high yields will require control of the process beyond the systems-level approaches reported so far. This presents an exciting frontier that exists at the intersection of these two communities -those who have studied the mechanistic details of catalytic processes relating to nucleation and growth of nanostructures, and those who are focused on systems-level directions to develop platforms which can address important global issues.…”
mentioning
confidence: 99%
“…The second step consisted of the reduction of the reactive carbon species on Cu foil at high temperature, thus producing graphene. Furthermore, approaches based on electrochemical methodologies using heterogeneous catalysts have been developed . For example, Hu et al.…”
Section: Introductionmentioning
confidence: 98%